Development of Student Worksheets Based on Integrated Field-Based Learning Using PlantNet in Teaching Plant Classification to Seventh Grade Junior High School Students - Aisyah, Al Fina Nurul; Hasanah, Rafiatul (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
The development of the digital era has encouraged the use of information and communication technology as one of the important pillars of 21st century learning innovation. Mobile phone-based applications such as PlantNet can be used to help students identify plants directly in their surroundings. Based on an analysis of student needs, 62% prefer practical-based instructional materials, 70% prefer mobile-based learning applications, and 84.6% opt for learning activities involving practical exercises. Plant classification material is still considered challenging by the majority of students. Science teachers noted that instruction remains predominantly lecture-based, relying on limited worksheets and textbooks. Teachers also suggested the development of more innovative instructional materials without abandoning the worksheet format. This study aims to describe the validity, practicality, and effectiveness of the PlantNet application-assisted practical workbook for seventh-grade plant classification material at SMPN 1 Jenggawah. The type of research used is Research and Development (R&D) with the ADDIE model. Data collection techniques include observation, interviews, questionnaires, and tests. The validation results showed a percentage of 88.1% (content) and 92.8% (media), falling into the highly valid category. Practicality reached 85.7% (teachers and students), as well as 94% and 90% from student trials. Effectiveness, based on the N-gain test, was 0.8 and 0.7, falling into the high category.